Agricultural Information and Land Grant Libraries: Past, Present, and Future. Issue 2 (3rd July 2019) - Level, Allison V.; Paster, Amy L.
Abstract: Land-grant libraries contribute to the national corpus of research through holdings of journals, books, e-books, conference proceedings, government documents, and more. Impacts on land-grant libraries and agricultural information and implications for the future landscape include a number of topics ranging from the role of journal package deals on collection development budgets to the importance of agriculturally focused professional societies. The agricultural information outlook for the future is being cultivated today. New and current information is critical but the preservation of the agricultural heritage is a necessary part of the plan.